Strategi Pemasaran Produk Cicilan Emas Pada BSI Kantor Kas Darul Ulum - Lailiyah, Nurul; Susilawati, Ririn; Suspahariati (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2025)
This study aims to examine the marketing strategies implemented by Bank Syariah Indonesia (BSI) in promoting its Gold Installment product. This product offers Sharia-compliant financing for gold bullion purchases through a murabahah (cost-plus sale) contract, allowing customers to invest in gold in a safe, affordable, and Islamic way. BSI applies marketing strategy, which include offline and online. The analysis reveals that the integrated application of the 7P strategy significantly enhances the competitiveness of the Gold Installment product amid the rising trend of gold investment. Digital service innovations, customer education through Sharia-based promotions, and simplified procedures are key factors in attracting customer interest. With the right marketing approach, BSI successfully positions itself as a modern Islamic bank that is adaptive and committed to meeting the financial needs of the Muslim community